Pengaruh Jumlah Siklus Dip-Drying Pada Sintesis Koating Tembaga-Kobalt Oksida Berbasis Nitrat Konsentrasi Tinggi Sebagai Solar Selective Absorber Dengan Metode Sol-Gel Dip-Coating - Benny Ahmadi; Amun Amri; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Solar Selective Absorber (SSA) is the most important part that determines the efficiency of solar thermal collectors. SSA should have high absorptance (low reflectance at wavelengths <2.5 m) and low emitance (high reflectance at wavelengths> 2.5 m). Solar selective absorber can be synthesized using sol-gel dip coating method. The purpose of this research is to know the effect variation number of dipping-drying cycles to absorptance copper-cobalt coating and get a coating of copper cobalt that have absorptance value is high (> 80%) and low emitance (<10%). The coating were synthesized by molar percursors 0.25:0.5M and number of dipping-drying cycles 1x, 2x, 3x, 4x, 6x, 8x and 10x. Reflektance spectra in the area of UV-Vis-NIR showed that increased cycles of dipping-drying cycles (which increases the thickness of the coating) increase the value of absorptance (α). The results showed that the highest absorptance value found in coatings which was synthesized using mixture copper nitrate and cobalt nitrate 0.25:0.5M M at 2x cycles (dipping and drying) with absorptance (α) = 84.90%. Further characterization showed emitance values (ε) = 13.2%.Keywords : aluminum, coating, solar selective absorber and sol-gel dip-coating